ASUHAN KEPERAWATAN KELUARGA PADA NY.S KHUSUSNYA NY.S DENGAN MASALAH KESEHATAN HERNIA NUCLEUS PULPOSUS DI RT 05 RW 07 KELURAHAN LIMO KOTA DEPOK - Athifah Dinda Fitriyah, (2023)
Background : HNP (Hernia Nucleus Pulposus) is a condition where the contents of the nucleus pulpousus are expelled from the intervertebral disc so that the mucleus of the disc protrudes into the annular ring and gives symptoms of nerve compression in the form of pain. Purpose : This research was conducted to gain experience and a real picture in providing family nursing care to patients with HNP (Hernia Nucleus Pulposus) which includes assessment, nursing diagnosis, nursing plan, nursing implementation and nursing evaluation. Method : The research design used was a descriptive method in the form of a case study in implementing nursing care for patients with HNP (Hernia Nucleus Pulposus) in Rt 05 Rw 07 Limo Village, Depok City. Data collection was carried out by interviews, observation and physical examination as well as documentation studies. Results : The nursing problems found in cases were chronic pain related to the inability of families to care for family members with nerve compression problems, impaired physical mobility related to the inability of families to care for family members with neuro-muscular problems, ineffective family health management related to family disabilities in recognizing health problems of family members. After carrying out nursing actions for 3x24 hours the results of the evaluation of all nursing problems can be resolved. Conclusion : It is hoped that further research can provide good and appropriate nursing care for patients with HNP (Hernia Nucleus Pulposus) so that it is in accordance with the nursing problems found in patients.